Effects of diet bulk density on mixing uniformity - Lori L Thomas; Charles R Stark; C H Fahrenholtz; Kyle F Coble; S Hayashi; Marut Saensukjaroenphon; Jason C Woodworth; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2014)
The objective of this study was to determine how the time required to create a uniformly mixed batch of feed is influenced by diets that differ in bulk density. Three 60-lb batches of a corn-soybean meal—based diet (high bulk density) or a high-fiber diet (low bulk density) containing 30% dried distiller's grains with solubles (DDGS), and 19% wheat midds were prepared. The ingredients for each batch were placed in a 60-lb capacity experimental double-ribbon mixer with all batches containing 0.35% table salt. Ten samples were obtained from different parts of the mixer for each batch of feed after 60, 120, and 240 sec of mixing time. Ten additional samples were taken as the feed was discharged from the bottom of the mixer after 240 sec. The three batches of each diet type were mixed and sampled using the same procedures and were considered separate observations, making 3 replications for each mixing time within diet type. The CV among 10 samples collected at each mix time was used to determine mixer efficiency by measuring Cl concentration (Quantabs, Environmental Test Systems, Elkhart, IN). After 60 sec of mixing, the corn-soybean meal—based diet achieved a CV of less than 10%; however, the high-fiber diet required 240 sec to achieve a CV of less than 10%. In conclusion, using this experimental ribbon mixer, diet bulk density affected the time required to mix a batch of feed thoroughly, which suggests that feed manufacturers should reevaluate mixing times when using low-bulk-density ingredients such as DDGS and wheat midds. Further research is needed to verify these results in large-scale commercial mixers.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Bulk density; Diet type; Mixing efficiency